Pectin-based bioinks for 3D models of neural tissue produced by a pH-controlled kinetics - Merli, Marta; Sardelli, Lorenzo; Baranzini, Nicolò; Grimaldi, Annalisa; Jacchetti, Emanuela; Raimondi, Manuela Teresa; Briatico-Vangosa, Francesco; Petrini, Paola; Tunesi, Marta (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract: In the view of 3D-bioprinting with cell models representative of neural cells, we produced inks to mimic the basic viscoelastic properties of brain tissue. Moving from the concept that rheology provides useful information to predict ink printability, this study improves and expands the potential of the previously published 3D-reactive printing approach by introducing pH as a key parameter to be controlled, together with printing time. The viscoelastic properties, printability, and microstructure of pectin gels crosslinked with CaCO3 were investigated and their composition was optimized (i.e. by including cell culture medium, HEPES buffer, and collagen). Different cell models representative of the major brain cell populations (i.e. neurons, astrocytes, microglial cells, and oligodendrocytes) were considered. The outcomes of this study propose a highly controllable method to optimize the printability of internally crosslinked polysaccharides, without the need for additives or post-printing treatments. By introducing pH as a further parameter to be controlled, it is possible to have multiple (pH-dependent) crosslinking kinetics, without varying hydrogel composition. In addition, the results indicate that not only cells survive and proliferate after 3D-bioprinting, but they can also interact and reorganize hydrogel microstructure. Taken together, they suggest that pectin-based hydrogels could be successfully applied for neural cell culture.